Polynomial Function on Fourier Cosine and Sine Transform (Global Journal of Science Frontier Research, 2018)
Aim of this study is to provide properties of a polynomial function on Fourier cosine and Fourier sine transform. Authors presented general properties of a polynomial function on Fourier cosine and Fourier sine transform by applying known results.
Keywords: fourier cosine and sine transform; polynomial function